META-SYNTHESIS: TRI HITA KARANA A PHILOSOPHY OF HARNESS AND LIFE HARMONY - Ida Ermiana; I Made Sutajaya; I Wayan Suja; Asri Fauzi (PROGRES PENDIDIKAN, 2023)
Harmony in the life of the state, society and family really needs to be nurtured and preserved from an early age. Harmony is not only in religion, but in all things in life. Considering that the Indonesian state consists of many religions (six religions and belief systems), many islands, many customs, many languages and many tribes in it. Harmony is a peaceful and peaceful life in living a social life of mutual tolerance between people with one another, both of the same religion or different religions, so as to create harmony in life. The purpose of this study is to describe the implementation of Tri Hita Kirana in the world of work, education and socio-cultural society. Meta-synthesis as a qualitative systematic review method with a meta-aggregation approach is the method of choice for this research. There are ten Tri Hita Karana articles reviewed. Tri Hita Karana as a philosophy of view of life that can be used as a philosophical foundation for living in harmony, creating a harmonious relationship with God, harmonious human-human relations, and human-human relations with the universe. If harmony has been created starting from the smallest scope, namely family, society and country, then tolerance and harmony in life will create happiness on earth. Tri Hita Karana can be implemented in the world of work, education and socio-cultural.